2023
DOI: 10.15581/003.36.3.119-132
|View full text |Cite
|
Sign up to set email alerts
|

«I heard about some pills»: the online as a sharing space and source of information about performance consumption among students

Abstract: Departing from a broader sociological study, this article presents exploratory research seeking to analyse practices of online information exchange on the consumption of medicines and food supplements among students, mainly to improve cognitive performance. It aims to show that the Internet is a relevant space which should be considered when analysing where lay people, specifically students, get information about medicines. The empirical field was limited to online open discussion forums, websites, and blogs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…This tallies with results from previous research in Portugal, which found these sources to be the most highly valued (Clamote 2010). While the internet has been gaining some relevance as a source of information about medications, the data suggest that it is not a direct trigger for consumption but rather a way to initially access information that is later validated with expert interpersonal sources (Egreja et al 2023). The fact that people prefer direct contact with experts, as opposed to impersonal institutional channels, attests to the continuing importance of an interpersonal dimension in the construction of trust in information about medications (Rodrigues 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This tallies with results from previous research in Portugal, which found these sources to be the most highly valued (Clamote 2010). While the internet has been gaining some relevance as a source of information about medications, the data suggest that it is not a direct trigger for consumption but rather a way to initially access information that is later validated with expert interpersonal sources (Egreja et al 2023). The fact that people prefer direct contact with experts, as opposed to impersonal institutional channels, attests to the continuing importance of an interpersonal dimension in the construction of trust in information about medications (Rodrigues 2021).…”
Section: Discussionmentioning
confidence: 99%